2016
DOI: 10.4062/biomolther.2016.011
|View full text |Cite
|
Sign up to set email alerts
|

Skin Barrier Recovery by Protease-Activated Receptor-2 Antagonist Lobaric Acid

Abstract: Atopic dermatitis (AD) results from gene and environment interactions that lead to a range of immunological abnormalities and breakdown of the skin barrier. Protease-activated receptor 2 (PAR2) belongs to a family of G-protein coupled receptors and is expressed in suprabasal layers of the epidermis. PAR2 is activated by both trypsin and a specific agonist peptide, SLIGKV-NH2 and is involved in both epidermal permeability barrier homeostasis and epithelial inflammation. In this study, we investigated the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…Another study found that the corneal epithelial barrier function could be altered by PAR2 activation [Li et al, ]. The skin barrier function could be compromised by PAR2 activation [Joo et al, ]. Our data are in line with these pioneer studies by showing that activation of PAR2 compromise epithelial barrier integrity.…”
Section: Discussionsupporting
confidence: 91%
“…Another study found that the corneal epithelial barrier function could be altered by PAR2 activation [Li et al, ]. The skin barrier function could be compromised by PAR2 activation [Joo et al, ]. Our data are in line with these pioneer studies by showing that activation of PAR2 compromise epithelial barrier integrity.…”
Section: Discussionsupporting
confidence: 91%
“…IVL is synthesized in the spinal cell layer and cross-linked with granulosa cells under the action of glutamine transferase to form an important structural support for the skin barrier (45). At present, IVL is mostly used as a marker protein to study skin keratinocyte differentiation (46,47). However, there are few reports of the associations between integrin and melanoma (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…IVL is synthesized in the spinal cell layer and cross-linked with granulosa cells under the action of glutamine transferase to form an important structural support for the skin barrier [42]. At present, IVL is mostly used as a marker protein to study skin keratinocyte differentiation [43,44], however, there are few reports of the associations between integrin and melanoma. In view of its important role in maintaining skin function, we can speculate that IVL may also play an important role in the progression of melanoma.…”
Section: Discussionmentioning
confidence: 99%